Evaluating insect turnover through the zeta diversity framework to determine corridor effectiveness for biodiversity conservation in South African plantation forestry - Lategan, Trevor Daniel (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScConsEcol)--Stellenbosch University, 2026.